An unexpected recovery of patients with pulmonary arterial hypertension and SARS-CoV-2 pneumonia: a case series. (September 2020) - Scuri, Piermario; Iacovoni, Attilio; Abete, Raffaele; Cereda, Alberto; Grosu, Aurelia; Senni, Michele
Since the beginning of the SARS-CoV-2 outbreak, few cases of COVID-19 pneumonia in patients with pulmonary arterial hypertension have been reported. We present four patients with known history of PAH admitted to our hospital with SARS-CoV-2 pneumonia to analyze the impact of this disease on their clinical outcome.